Effects of Gypsum and Limestone on Early-Age Hydration and Strength Optimization in Belite Calcium Sulfoaluminate Cement - Sai Akshay Ponduru; Bryan K. Aylas-Paredes; Taihao Han; Advaith Neithalath; Narayanan Neithalath; Gaurav Sant; Aditya Kumar (Infrastructures)
Belite calcium sulfoaluminate cement (CSAB), an alternative to Portland cement, exhibits excellent strength at both early and later ages. However, due to its high belite content, the carbon reduction from this type of cement is not sufficient when compared to other alternative cements. To further enhance CSAB’s sustainability, this study investigates the performance of CSAB when partially replaced by low-carbon mineral additives (i.e., limestone and gypsum). The primary objective is to identify the optimal mixture design by incorporating gypsum and limestone to formulate a sustainable binder that maintains high compressive strength. The CSAB is replaced (with both additives) by up to 51% at two different liquid-to-solid ratios of 0.4 and 0.5. gypsum replacements ranging from 0% to 27%, resulting in three unique gypsum-to-ye’elimite molar ratios (M). Limestone replacements range from 0% to 30% in 10% increments. The investigation focuses on the development of hydrates, hydration kinetics, and compressive strength of the sustainable binders after 3 days. The results indicate that a higher replacement level of limestone provides more free water to react with ye’elimite and belite, thereby enhancing the hydration kinetics, but decreasing the compressive strength. It also shows that the addition of gypsum enhances the formation of ettringite, enabling the maintenance of great compressive strength within the binder even at high limestone replacement levels. The binder containing 12% gypsum and 20% limestone was identified as the optimal mixture, yielding a compressive strength of 39 MPa. This performance, when compared to the plain CSAB (compressive strength of 49 MPa), demonstrates that the optimized binder achieves adequate sustainability while maintaining mechanical properties without significant compromise.